Abdush Samad Al-Falimbani dalam Wacana Sejara Intelektual - M. Ma'ruf Misbah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2009)
Abdush Shamad a-Falimbani is a notorious scholar in the 18th century. He traveled to learn at di verse scientific centers. He studied various disciplines; thereby being a successful learned man,devoted Sufi, gifted teacher, and productive writer. He wrote various books that draw his thoughts. These past activities of al-Falimbani become important resources for research in the intellectual historiography of Islam. This article shows this significance.